PENERAPAN ASESMEN AUTENTIK BERBASIS TERTULIS UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF IPAS SISWA SDN TAGUNGGUH 2 - Aulia, Marsha; A, Jennie Salsabila; Helmia, Indi; Siswoyo, Andika Adinanda (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2025)
This study addresses the issue of low cognitive learning outcomes in IPAS (Science, Social Studies, and Arts) among fourth-grade students at SDN Tagungguh 2, where initial scores averaged only 64%. The research specifically focuses on improving these learning outcomes through the implementation of authentic written assessment integrated with the Discovery Learning model. Conducted as a three-cycle classroom action research (CAR), each stage meticulously involved planning, adaptive action implementation, detailed observation, and in-depth reflection. Data were collected using cognitive learning outcome tests (multiple-choice and essay) and observation sheets for teacher and student activities. In Cycle I, the average cognitive learning outcome was 64% with 42% mastery. Entering Cycle II, the addition of video media prompted an increase in the average to 75.8% and mastery to 61%. The peak improvement was achieved in Cycle III, where the use of information board media significantly boosted the average to 83% with 94% classical mastery. These findings unequivocally demonstrate the effectiveness of authentic written assessment synergized with Discovery Learning and educational media in developing students' conceptual understanding and critical thinking skills. This research recommends adapting similar approaches for future IPAS learning innovations. ABSTRAKPenelitian ini mengkaji permasalahan rendahnya hasil belajar kognitif IPAS dilakukan di kelas IV SDN Tagungguh 2 yang pada kondisi awal menunjukkan rata-rata hanya 64%. Penelitian ini secara spesifik berfokus pada peningkatan hasil belajar tersebut melalui implementasi asesmen autentik berbasis tertulis yang terintegrasi dengan model Discovery Learning. Sebagai penelitian tindakan kelas (PTK) tiga siklus, setiap tahapannya mencakup perencanaan yang cermat, pelaksanaan tindakan yang adaptif, observasi yang detail, dan refleksi mendalam. Data dikumpulkan melalui tes hasil belajar kognitif (pilihan ganda dan uraian) serta observasi aktivitas guru dan siswa. Pada siklus I, rata-rata hasil belajar kognitif tercatat 64% dengan ketuntasan 42%. Memasuki siklus II, penambahan media video mendorong peningkatan rata-rata menjadi 75,8% dan ketuntasan 61%. Puncak peningkatan dicapai pada siklus III, di mana penggunaan media papan informasi secara signifikan mendongkrak rata-rata hingga 83% dengan ketuntasan klasikal 94%. Temuan ini secara tegas membuktikan efektivitas asesmen autentik berbasis tertulis yang disinergikan dengan Discovery Learning serta media edukatif dalam mengembangkan pemahaman konseptual dan keterampilan berpikir kritis siswa. Penelitian ini merekomendasikan adaptasi pendekatan serupa untuk inovasi pembelajaran IPAS di masa mendatang.